2020
DOI: 10.1177/1535370220960675
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia–CXCL6 axis affects arteriolar niche remodeling in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is a malignant clonal disease derived from hematopoietic stem/progenitor cell. Leukemia blasts cause extensive hypoxia of bone marrow (BM), which lead to disorder and remodeling of BM niche, thereby becoming “leukemic niche” to support the development and drug-resistance of AML as well as the maintenance of normal hematopoietic stem cells. In this study, the biological characteristics (such as self-renewal, apoptosis, migration, autocrine) and function (vascularization) of mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…CXCLL2 deletion from the vascular endothelial vascular niche in T cell acute lymphoblastic leukemia impeded tumor growth ( Pitt et al, 2015 ). The chemokine CXCL6 promoted angiogenesis to remodel the arteriolar niche in acute myeloid leukemia ( Li et al, 2021 ).…”
Section: Part Three: Changes In Vascular Endothelial Nichesmentioning
confidence: 99%
“…CXCLL2 deletion from the vascular endothelial vascular niche in T cell acute lymphoblastic leukemia impeded tumor growth ( Pitt et al, 2015 ). The chemokine CXCL6 promoted angiogenesis to remodel the arteriolar niche in acute myeloid leukemia ( Li et al, 2021 ).…”
Section: Part Three: Changes In Vascular Endothelial Nichesmentioning
confidence: 99%
“…Yang et al found that IL-8 can activate Matrix Metalloproteinases (MMPs), Protein kinase B (Akt) and other downstream signaling pathways by binding CXCR1/CXCR2, and participate in the process of tumor cell proliferation and tumor angiogenesis [24] . Li et al found that the disorder of CXCL6/CXCR2 system in low hypoxia leads to inhibition of vascular remodeling and aggravate the process of vascular injury [25] . Yu et al found that CXCL5/CXCR2 can aggravate the ischemia-reperfusion injury of human microvascular endothelial cells [26] .…”
Section: Table 2: Docking Table Of Traditional Chinese Drug-ingredien...mentioning
confidence: 99%
“…Collectively, hypoxia is considered an adverse factor affecting the prognosis of AML ( Clarke and Fisher, 2019 ), as leukemic cells induce bone marrow hypoxia that results in the remodeling of the bone marrow niche ( Li et al, 2021a ). However, the effects of hypoxia on TIME and drug resistance in AML as well as the specific evaluation value of hypoxia-related genes in the clinical prognosis of AML remain unclear.…”
Section: Introductionmentioning
confidence: 99%